Assessment of body composition in adults hospitalized with acute COVID-19: a scoping review - das Virgens, Isabel Pinto Amorim; Sousa, Iasmin Matias; Bezerra, Agnes Denise Lima; Fayh, Ana Paula Trussardi (Frontiers in Nutrition, 2023)
Body composition (BC) assessment can add accurate information for in-hospital nutritional evaluation. The aim of this study was to explore in the literature how the studies assessed BC, for what purpose, and investigate the role of BC findings in COVID-19 hospitalized patients’ outcomes. A scoping review was conducted according to the methodology available on Joanna Briggs Institute (JBI) website. We used the PCC acronym for the systematic search (population-adults with COVID-19, concept- assessment of BC, context–hospital setting) and performed it on Pubmed, Scopus and Web of Science on September 16th, 2022. Eligibility criteria consisted in the utilization of BC assessment tools in COVID-19 patients. Studies in which BC was solely measured with anthropometry (perimeters and skinfolds) were excluded. No language restriction was applied. Fifty-five studies were eligible for the review. Out of the 55 studies, 36 used computed tomography (CT), 13 used bioelectrical impedance (BIA), and 6 used ultrasound (US). No studies with D3-creatinine, 24h urine excretion, dual-energy X-ray absorptiometry, or magnetic resonance were retrieved. BC was mainly assessed to test associations with adverse outcomes such as disease severity and mortality. Studies assessing BC in hospitalized patients with COVID-19 used mainly CT and BIA and associated the parameters with severity and mortality. There is little evidence on BC assessed by other methods, as well as studies on BC changes during hospitalization.